Juvenile rheumatoid arthritis and del(22q11) syndrome: a non-random association. Issue 11 (November 1998) - Verloes, A; Curry, C; Jamar, M; Herens, C; O'Lague, P; Marks, J; Sarda, P; Blanchet, P
Abstract : Del(22q11) is a common microdeletion syndrome with an extremely variable phenotype. Besides classical manifestations, such as velocardiofacial (Shprintzen) or DiGeorge syndromes, del(22q11) syndrome may be associated with unusual but probably causally related anomalies that expand its phenotype and complicate its recognition. We report here three children with the deletion and a chronic, erosive polyarthritis resembling idiopathic cases of juvenile rheumatoid arthritis (JRA). Patient 1, born in 1983, initially presented with developmental delay, facial dysmorphism, velopharyngeal insufficiency, and severe gastro-oesophageal reflux requiring G tube feeding. From the age of 3 years, he developed JRA, which resulted in severe restrictive joint disease, osteopenia, and platyspondyly. Patient 2, born in 1976, had tetralogy of Fallot and peripheral pulmonary artery stenosis. She developed slowly, had mild dysmorphic facial features, an abnormal voice, and borderline intelligence. JRA was diagnosed at the age of 5 years. The disorder followed a subacute course, with relatively mild inflammatory phenomena, but an extremely severe skeletal involvement with major osteopenia, restrictive joint disease (bilateral hip replacement), and almost complete osteolysis of the carpal and tarsal bones with phalangeal synostoses, leading to major motor impairment and confinement to a wheelchair. Patient 3, born in 1990, has VSD, right embryo-toxon, bifid uvula, and facial dysmorphism. She developed JRA at the age of 1 year. She is not mentally retarded but has major speech delay secondary to congenital deafness inherited from her mother. In the three patients, a del(22q11) was shown by FISH analysis. These observations, and five other recently published cases, indicate that a JRA-like syndrome is a component of the del(22q11) spectrum. The deletion may be overlooked in those children with severe, chronic inflammatory disorder.